Genetically modified foods: Consumer awareness, opinions and attitudes in selected EU countries. (26th February 2017) - Popek, Stanisław; Halagarda, Michał
Abstract: The dynamic development of biotechnology in recent years has raised serious public concerns about the possible risks arising from genetically modified organisms (GMOs). The aim of this study was to investigate consumer opinions regarding genetically modified (GM) foods. The research also aimed at verifying the differences in the attitudes of respondents from two, relatively culturally diverse research sites. To obtain empirical data a face‐to‐face survey was conducted in 2015. It covered a total of 976 randomly selected individuals. The study was performed in the capital of the United Kingdom—London and the Polish capital—Warsaw. The results of the study show that almost half of the respondents were familiar with the GMO concept. According to the respondents, the greatest benefits arising from the genetic modification are: enhanced shelf‐life of food and crops' resistance to extreme climatic conditions. The main disadvantages were: unpredictable consequences of deoxyribonucleic acid (DNA) modification, production of species‐specific toxins and food allergenicity. Over two thirds of people surveyed support the idea of the obligatory labeling of GM foods. The information presented on food packaging should primarily include potential contraindications to the consumption, indication that food was produced using transgenic sources and a warning about potential allergenicity. An almost equal number of respondents showed intention for purchasing GM food products, an intention to act otherwise, or was not decided. As many as 27.7% of survey participants showed negative attitudes toward GM foods, whereas only 19.8% predominantly positive. It is worth noticing that, with only one exception, no statistically significant differences were observed between the opinions of Polish and British respondents.